Web-Based and QR-Code Thesis Information System in the Faculty of Computer Science University Bina Darma - Anjelina Anjelina; Ilman Zuhri Yadi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Information systems as part of the development of information technology are needed to shape the performance of an agency. Currently, the thesis data of the Faculty of Computer Science at Bina Darma University is not well structured because there is no system that regulates it so that it cannot be used by students and lecturers to view thesis data for the Faculty of Computer Science at Bina Darma University. This often makes students experience several problems such as the difficulty of finding references for thesis references for alumni of the Faculty of Computer Science because there is no system that regulates and stores student thesis data, so we need a web-based system to make it easier for students and lecturers to see a collection of thesis for alumni of the Faculty of Computer Science. In developing this system using the Web and QR Code so that it can help students and lecturers in searching for thesis data quickly. The system development method that the author uses is the waterfall method. This system uses the PHP programming language and as a user interface design for the database using XAMPP with Mysql as the server configuration. The output produced from this development is an information system that can provide information in the form of a collection of thesis of the Faculty of Computer Science by utilizing the Web and QR Code.